2019
DOI: 10.1016/j.jped.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Delays in the health care system for children, adolescents, and young adults with bone tumors in Brazil

Abstract: Health care delay among patients with a previous diagnosis was longer, and was probably associated with the time taken for to referral to cancer centers. Patients without a previous histopathological diagnosis had longer hospital delays, which could be associated with possible difficulties regarding demand and high-cost procedures. Despite limitations, this study helps provide initial knowledge about the healthcare pathway delays for patients with bone cancer inside several Brazilian hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Four other studies reported similar results on total intervals for Ewing sarcoma and osteosarcoma; all had a trend towards a longer diagnostic pathway for patients with Ewing sarcoma 12 14 26 40. In a study by Widhe et al (n=106), the longer diagnostic pathway in Ewing sarcoma was a result of both a longer patient and primary care component12 whereas a study by Sneppen et al (n=124), reported a four times longer diagnostic interval for Ewing sarcoma than for osteosarcoma patients despite similar patient intervals 26.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Four other studies reported similar results on total intervals for Ewing sarcoma and osteosarcoma; all had a trend towards a longer diagnostic pathway for patients with Ewing sarcoma 12 14 26 40. In a study by Widhe et al (n=106), the longer diagnostic pathway in Ewing sarcoma was a result of both a longer patient and primary care component12 whereas a study by Sneppen et al (n=124), reported a four times longer diagnostic interval for Ewing sarcoma than for osteosarcoma patients despite similar patient intervals 26.…”
Section: Resultsmentioning
confidence: 87%
“…Gender was not associated with the length of the total interval in four studies,12 26 39 40 however, there was evidence that patient age was a factor. Six studies reported a significantly longer total interval for older teenagers, adolescents or adults compared with younger children or (younger) teenagers (<12 vs ≥12–22 years1122; <20 vs ≥20–86 years26; <22 vs ≥22 years27; 0–14 vs 15–19 vs 20–29 years40; <12 versus ≥12 years11). Furthermore, Desandes et al found young adults were more at risk for a longer total interval than patients in puberty (15–19 vs 20–24 years; 10.1 vs 21.4 weeks respectively; p=0.04) 35.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Com o intuito de evitar atrasos no processo entre a suspeição diagnóstica e a instituição terapêutica, recomenda-se que o paciente seja encaminhado ao serviço de referência na iminência da suspeita a fim de realizar o diagnóstico e, logo em seguida, iniciar o tratamento na mesma instituição, pois estudos apontaram que a necessidade de transferência após o diagnóstico se correlaciona com a extensão do tempo até o tratamento 15,16,20,24 . Tal achado pode ser em razão da demora no encaminhamento e da necessidade de percorrer maiores distâncias até a instituição que fornecerá o tratamento, o que pode implicar custos durante o deslocamento e estada do paciente e seu responsável, além da possível necessidade de este se ausentar temporariamente de suas atividades laborais, gerando impactos em todo o seio familiar.…”
Section: Discussionunclassified